PENINGKATAN HASIL BELAJAR DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DI SEKOLAH DASAR - Oktavia, Winda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research background of the fact that learning in elementary school is often dominated by the teacher as a source of information based on observation the researchers found low student learning outcomes. Here researchers using CTL approach to improve student learning outcomes. The purpose of this research to improve learning outcomes approach Civics using Contextual Teaching and Learning (CTL) in class IV SDN 34 Pasar Durian Lubuk Basung Agam District. The study was Classroom Action Research (CAR). This study uses four stages of action, namely the planning, action, observation and reflection. The data source is the process of implementation of CTL approach learning in class IV Elementary School District 34 Pasar Durian Lubuk Basung Agam District. Subjects were fourth grade students totaling 16 people. Data collection techniques used are observation, field recording, and engineering tests. The results showed the first cycle I and II meetings that RPP obtained from the assessment scores 71.4 and 78.6, from the aspect of teacher earned a score of 70 and 81.8, from the aspect of the students obtained a score of 65.9 and 82, student learning outcomes acquired nilsi was 57.7 and 88 cognitive, affective values ​​63 and 94, while the value psikomotornya are 60 and 82. While on the second cycle of assessment scores obtained RPP 96.4, from the aspect of teachers obtained a score 95.5, from the aspect of the students obtained a score of 93.2, obtained students' cognitive nilsi was 96, affective value of 97, while the value was 86 psikomotornya , it appears that student learning outcomes increased from cycle I to cycle II. Thus it was revealed that the use of CTL approach can improve learning outcomes Civics in the Elementary School fourth grade students 34 Pasar Durian Lubuk Basung Agam District. Kata kunci: hasil belajar, PKn, contextual teaching and learning (ctl)